Handbook of structural stability. Part VI, - Becker, Herbert, 1918- (National Advisory Committee for Aeronautics, 1958)
A comprehensive review of failure of stiffened curved plates and shells is presented.
NACA TN No. 3786.
Keywords: Structural analysis (Engineering); Stability.; Plates (Engineering) -- Curvature.; Shells (Engineering) -- Curvature.; Strength of materials.; Buckling (Mechanics); Loads (Mechanics); Strains and stresses.; elektronické knihy; electronic books